Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s12034-010-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent growth and optical properties of SnO2 nanowires and nanobelts

Abstract: SnO 2 nanowires and nanobelts have been grown by the thermal evaporation of Sn powders. The growth of nanowires and nanobelts has been investigated at different temperatures (750-1000°C). The field emission scanning electron microscopic and transmission electron microscopic studies revealed the growth of nanowires and nano-belts at different growth temperatures. The growth mechanisms of the formation of the nanostructures have also been discussed. X-ray diffraction patterns showed that the nanowires and nanobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 37 publications
(29 reference statements)
2
10
0
Order By: Relevance
“…IR spectra presented in Fig. 6 correspond well with the results published in the literature, especially since the 563 cm −1 band present in the 1D SnO 2 nanostructure in the current study was also reported to exist in 1D structures by others [23]. The presence of this extra absorption band in the 560–570-cm −1 region is known as a characteristic feature of 1D SnO 2 structures, but the nature of their presence still requires clarifications.
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…IR spectra presented in Fig. 6 correspond well with the results published in the literature, especially since the 563 cm −1 band present in the 1D SnO 2 nanostructure in the current study was also reported to exist in 1D structures by others [23]. The presence of this extra absorption band in the 560–570-cm −1 region is known as a characteristic feature of 1D SnO 2 structures, but the nature of their presence still requires clarifications.
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…There are many papers recently published that study either 0D or 1D nanostructured SnO 2 [ 15 , 16 , 23 , 24 ]. However, the direct comparison of performance of these structurally very different materials is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the accepted value of 3.60 eV for the energy-gap of the SnO 2 nanobelts [19,20] , the ionization energy of the acceptor and the donor level involved in the optical transitions eA° and DAP could also be determined to be, E A = 240 meV and E D1 = 80 meV. The donor level E D1 could also be defined by the IR-UV peaks, 2.07 and 1.47 eV, since both are broad peaks, the value of E D1 obtained was 60 meV, so in order to corroborate with the other transition the donor state were defined to be in the range of E D1 = 60-80 meV.…”
Section: Photoluminescence Experimentsmentioning
confidence: 99%
“…3(B) shows PL emission spectra, the emission peak appearing in all spectra at ~ 366 nm is usually attributed to the free exciton electron hole recombination [8]. The broad emission peak is suggestive of the formation of oxygen deficient nanostructured SnO 2 [9]. It also has been found that as the particle size increases the PL intensity decreases.…”
Section: Methodsmentioning
confidence: 93%